Minos: variant adjudication and joint genotyping of cohorts of bacterial genomes - Martin Hunt; Brice Letcher; Kerri M. Malone; Giang Nguyen; Michael B. Hall; Rachel M. Colquhoun; Leandro Lima; Michael C. Schatz; Srividya Ramakrishnan; CRyPTIC consortium; Zamin Iqbal (Genome Biology, 2022)
Abstract There are many short-read variant-calling tools, with different strengths and weaknesses. We present a tool, Minos, which combines outputs from arbitrary variant callers, increasing recall without loss of precision. We benchmark on 62 samples from three bacterial species and an outbreak of 385 Mycobacterium tuberculosis samples. Minos also enables joint genotyping; we demonstrate on a large (N=13k) M. tuberculosis cohort, building a map of non-synonymous SNPs and indels in a region where all such variants are assumed to cause rifampicin resistance. We quantify the correlation with phenotypic resistance and then replicate in a second cohort (N=10k).